Does selection index application for highly heritable traits need revisiting – A comprehensive study with bodyweight and shank length in Vanaraja male line chicken - RAJKUMAR, U; PRINCE, L L L; HUANSHI, S; JAYAKUMAR, S; RAVINDRA, K S RAJA; NIRANJAN, M; REDDY, B L N; CHATTERJEE, R N (The Indian Journal of Animal Sciences, 2023)
Selection index (SI) is one of the best methods for estimating the breeding value of an animal combining all sources of information on the animal and its relatives. In the present study, the SI was constructed utilizing the five generations data of Vanaraja male line (PD-1) for body weight (BW-6) and shank length (SL-6) at 6 weeks of age with variance, covariance estimates and heritability of both the traits. The SI was employed on three generations data on simulation basis and the selection parameters were estimated and compared with the mass selection (MS) actually practiced in the population. The least squares mean of SL-6, the primary trait of selection increased from 76.63±0.002 (G-I) to 82.85 ±0.002 mm (G-II), and subsequently reduced to 80.17±001 mm (G-III). The BW-6 also followed similar trend. Generation had significant effect on both SL-6 and BW-6. The heritability estimates for SL-6 and BW-6 were moderate with 0.21 to 0.28 for SL-6 and 0.22 to 0.27 for BW-6. The two traits exhibited high degree of positive association with 0.87 to 0.92 correlation coefficient. The economic value estimated for weight and shank length was 1:8.95. Thus, the selection index constructed was I= 0.2260*BW6, g + 0.7717*SL6, mm. Selection differential was higher in SI method on pooled basis compared to MS in all three generations for the primary trait, SL-6. The response to selection and selection intensity was also higher in SI method compared to MS. A similar trend was observed for BW-6 with respect to selection differential and response to selection. The study concluded that SI was superior to mass selection based on the results in Vanaraja male line chicken.